Fresno County Young Lawyers Hopper Luncheon Keynoter California Supreme Court Associate Justice Malcolm Lucas - Watkins, Howard::::::::: (1985)
Justice Donald Fransen, N. A. "Chad" Chaderjian, Justice Malcolm Lucas, Presiding Justice George Brown and Judge Blaine Pettitt Chaderjian was a Fresno County Probation Officer and led the California Youth and Adult Correctional Agency and Chaired the Board of Corrections